Buddhism: Analytical Explanation of Hell, Heaven, Reincarnation and Its Relevancy at Present Context - Sherpa, Rinju (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
This study entitled "Analytical Explanation of Hell, Heaven, Reincarnation and its Relevancy at Present Context" is based on primary and secondary data and the structured questions have been used to collect Primary data in Bhojpur Municipality- 9, Bhojpur. The main objectives of the study are to find out the real meaning of Hell, Heaven, Reincarnation, to find out the problems and its solutions. Primary and secondary sources have been adopted to achieve the objectives and to draw the conclusion. The study concludes that Hell and Heaven depends on our own karma (action). Desires is the cause of suffering, pain, unhappiness, violence, exploitation, diseases. Happiness is not obtained from matters. Happiness obtained from the matters is transitory and human as well as other creatures change their forms after death. It means nothing is stable or everything changes its forms.